Implementasi User Centered Design Pada Sistem Pakar Diagnosis Gangguan Perkembangan Motorik Kasar Pada Anak Usia Dini - Linda Perdana Wanti; Ifda Nurul Azroha; Muhammad Nur Faiz (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2019)
This study aims to build a knowledge-based psychology system for the diagnosis of gross motor development disorders in early childhood so that it can help educators in this case, PAUD teachers and parents/guardians in knowing information about gross motor development disorders in children. This study uses the development method of the UCD (User-Centered Design) system. The inference engine used is forward chaining that performs the search for progress in extracting information in this case, the symptoms that arise in children who are unusual with other children. The final results obtained from this study are an expert system for the diagnosis of gross motor development disorders in early childhood where the user chooses symptom data contained in the choice. Users will get the results of consultations in the form of conclusions about the diagnosis of the disorder and the implementation of the therapy.